Genes located in and near the human pseudoautosomal region are located in the X-Y pairing region in dog and sheep - Toder, Roland; Gläser, Birgitta; Schiebel, Katrin; Wilcox, S. A.; Rappold, Gudrun; Graves, J. A. M.; Schempp, Werner (Chromosome research, 1997)
We cloned and mapped the dog and/or sheep homologues of two human pseudoautosomal genes CSF2RA and ANT3. We also cloned and mapped dog and/or sheep homologues of STS and PRKX, which are located nearby on the differential region of the human X and have related genes or pseudogenes on the Y. STS, as well as CSF2RA, mapped to the tips of the short arm of the sheep X and Y (Xp and Yp), and STS and PRKX, as well as ANT3, mapped to the tips of the dog Xp and Y long arm (Yq). These locations within the X-Y pairing regions suggest that the regions containing all these human Xp22.3-Xpter genes are pseudoautosomal in dog and sheep. This supports the hypothesis that a larger pseudoautosomal region (PAR) shared by eutherian groups was disrupted by chromosomal rearrangements during primate evolution. The absence of STS and ANT3 from the sex chromosomes in two prosimian lemur species must therefore represent a recent translocation from their ancestral PAR, rather than retention of a smaller ancestral PAR shared by mouse.
Gesehen am 29.03.2021